2022
DOI: 10.31803/tg-20220203155555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non-Wood Fibres in Printed Paper Substrate on Barrier and Migration Properties

Abstract: Nowadays, there is a strong initiative to use recycled or biodegradable materials in all aspects of production including the graphic industry. In this study, paper was used as a material fulfilling the two of mentioned properties. Under laboratory conditions, papers were made of 70% pulp from recycled wood fibres with an addition of 30% straw pulp (wheat, barley or triticale). Considering the importance of the possibility of printing such media based on their end use, the influence of fibre type on vapour barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The use of alternative materials in papermaking offers a more sustainable and economically viable solution for reducing the consumption of wood pulp and minimizing the use of virgin fibers. Furthermore, using recycled and non-woody plants in paper production offers more advantages, like providing an environmentally friendly alternative to conventional wood-based paper manufacturing, reducing deforestation and CO 2 production [5,6]. Moreover, it allows for the reuse and recycling of paper, contributing to waste reduction and resource conservation [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of alternative materials in papermaking offers a more sustainable and economically viable solution for reducing the consumption of wood pulp and minimizing the use of virgin fibers. Furthermore, using recycled and non-woody plants in paper production offers more advantages, like providing an environmentally friendly alternative to conventional wood-based paper manufacturing, reducing deforestation and CO 2 production [5,6]. Moreover, it allows for the reuse and recycling of paper, contributing to waste reduction and resource conservation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ensuring an even density in the paper is influenced by various parameters such as the pulp preparation technology, equipment, and selection of optimal raw materials [13]. The availability of raw materials, especially non-wood materials, is a challenge due to the pressure on forests and the decline in capacity utilization in the paper industry [6]. Additionally, the influence of the fiber type on the vapor barrier properties and migration to foods needs to be considered for food packaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…Papers with an addition of cereal pulp are mostly used for secondary packaging (Kurek et al, 2022) which often contain some kind of printed content: text, barcodes, logos and other types of graphics. This research focuses on evaluating the quality of ink-jet printed text patterns for two different typefaces.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted on residual straw of wheat, barley and triticale collected after the crop harvest, and it has shown that cereal straw is a valuable raw material for the paper industry (Plazonić, Barbarić-Mikočević & Antonović, 2016;Plazonić, Barbarić-Mikočević & Džimbeg-Malčić 2014a;Plazonić, Barbarić-Mikočević & Džimbeg-Malčić 2014b). Papers with an addition of cereal pulp are mostly used for secondary packaging (Kurek et al, 2022) which often contain some kind of printed content: text, barcodes, logos and other types of graphics. This research focuses on evaluating the quality of ink-jet printed text patterns for two different typefaces.…”
mentioning
confidence: 99%